2016
DOI: 10.1007/s00277-016-2869-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of IKZF1 deletion in adult B cell acute lymphoblastic leukemia: a meta-analysis

Abstract: The IKAROS family zinc finger 1 (IKZF1) gene is frequently altered in adults with B cell acute lymphoblastic leukemia (ALL). Although many studies have indicated that IKZF1 alterations might be associated with poor outcomes in adults with ALL, the results remain controversial. A previous meta-analysis demonstrated the negative prognostic significance of IKZF1 deletion in ALL. However, most of the included studies (14 out of 15) were conducted in pediatric patients with ALL, and age was identified as a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…This analysis identified several well‐known B cell‐associated proteins including BAX, BCAP31, BCLAF1, CD44, CD47, CD53, LYN, PPIB, PTPRCAP, PTPRC and SYK. We also identified other leukaemia associated proteins IKZF1 (Zhang et al , ), LASP1 (Frietsch et al , ) and ARHGEF12 (Dirse et al , ). We did not identify CD19, probably due to the location of the trypsin cut sites resulting in a low number of peptides available for identification; this is supported by the fact that Alsagaby et al () also lacked CD19 identification in their MS analysis of B‐CLL cells.…”
Section: Resultsmentioning
confidence: 72%
“…This analysis identified several well‐known B cell‐associated proteins including BAX, BCAP31, BCLAF1, CD44, CD47, CD53, LYN, PPIB, PTPRCAP, PTPRC and SYK. We also identified other leukaemia associated proteins IKZF1 (Zhang et al , ), LASP1 (Frietsch et al , ) and ARHGEF12 (Dirse et al , ). We did not identify CD19, probably due to the location of the trypsin cut sites resulting in a low number of peptides available for identification; this is supported by the fact that Alsagaby et al () also lacked CD19 identification in their MS analysis of B‐CLL cells.…”
Section: Resultsmentioning
confidence: 72%
“…However, Heyman et al (30) found that CDKN2A/B was significantly associated with poor prognosis in 79 pediatric B-ALL patients. In study of Messina et al, CDKN2A/B deletion had impact of DFS in only adult cohort of B-NEG ALL (26). Owing to its high deletion incidence in adult B-ALL, we also analyzed the prognosis of patients with CDKN2A/B gene deletion and 13) defined IKZF1 plus and proposed it as an MDR-dependent, poor prognostic profile in pediatric B-ALL.…”
Section: Discussionmentioning
confidence: 93%
“…However, Stanulla et al (13) and other studies (18,19) suggested that although the prognosis of pediatric B-ALL with IKZF1 deletion was poor, the OS of pediatric B-ALL with IKZF1 deletion was satisfactory, and hence, its prognostic significance was limited. Zhang et al (26) conducted a meta-analysis on eight national and international studies about the prognosis of IKZF1 gene deletion in adult B-ALL and speculated that IKZF1 gene deletion indicates poor prognosis; however, this prognostic significance only exists in patients with Ph -B-ALL. Moreover, as Messina et al reported, the outcome of IKZF1 deletion did not differ from that of IKZF1-WT patients both in pediatric and adult B-NEG ALL (B-ALL patients negative for the recurrent fusion transcripts, BCR-ABL, ETV6-RUNX1, TCF3-PBX1, KMT2A-rearrangement) (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this arrayCGH/SNPs showed three regions with biallelic deletion: 7p‐ including IKZF1 gene, 9p‐ involving CDKN2A / B and 13q‐encompassing RB1 gene, all considered to be negative prognostic factors in ALL. 15 , 16 , 17 , 18 , 19 , 20 To confirm the presence of only duplicated clone at diagnosis, we performed iFISH analysis using an XL BCR/ABL1 probe (MetaSystems) on the bone marrow smear and revealed 97% of cells showed normal findings of two signals for both ABL1 and BCR genes. This finding confirmed a clone detected by karyotyping with partial duplication of chromosomes 21 and X and with trisomy of chromosome 8 (Figure [Link] , [Link] ).…”
Section: Case Reportmentioning
confidence: 99%